Exothermic Supercooled Liquid-Liquid Transition in Amorphous Sulfur - 张豆豆 刘秀茹 洪时明 李良彬 崔昆朋 邵春光 何竹 徐济安 (Chinese physics letters, 2014)
Amorphous sulfur （a-S） is prepared by rapidly compressing molten sulfur to high pressure. From differential scanning calorimeter measurements, a large exothermic peak has been observed around 396K. Online wide-angled x-ray scattering spectra indicate that no crystallization occurs in the temperature range 295-453K, suggesting that the exothermal process corresponds to an amorphous-to-amorphous transition. The transition from amor- phous sulfur to liquid sulfur is further verified by the direct observation of sulfur melt at the temperature of the associated transition. This is the first time of reporting that a-S transforms to liquid sulfur directly, which has avoided a crystallization process. What is more, the transition is an exothermic and a volume expansion process.